Augmentation of Distal Antebrachial Non-union Healing in a Bitch with Local Application of Erythropoietin - Garnoeva, Radka Stayova; Vasileva, Radina (Acta Scientiae Veterinariae, 2024)
Background: The clinical management of non-unions relies on osteogenic, osteoinductive, osteoconductive properties of autologous bone grafts. Recently, the augmentation of fracture healing assumed paramount importance in modern orthopaedics, particularly in the management of non-unions with extensive bone defects. This report presents a clinical case of a Pomeranian with atrophic non-union of distal antebrachial bones treated with cancellous bone graft mixed with erythropoietin. The autologous grafts provides live osteogenic cells, whereas erythropoietin apart from attracting osteoblasts at the fracture site, improved blood supply due to its angiogenic potential. Case: A 11-month-old intact bitch Pomeranian, was referred for orthopaedic examination 1 day after traumatic injury following jump from a height. The patient had fracture of distal antebrachial bones accompanied with grade IV weight- bearing lameness and swelling, as well as severe pain and crepitus on palpation. The bitch was initially treated with dynamic compression plate and screws. Thirty-six days after the osteosynthesis, the patient was brought with severe pain and swelling of the operated limb, high-grade lameness, osteolytic areas due to implant loosening, severe thinning of compact bone and bone callus paucity. During the operative revision, existing implants were removed. The bone holes from screws and the bone defect were filled with autologous cancellous bone harvested from the proximal humerus, mixed with recombinant human erythropoietin for stimulation of bone healing. After the surgery, the limb was immobilized with a rigid splint and the patient spent 10 days in a cage for restriction of movements. The post operative period was smooth and as early as the 12th post-operative day, the animal was discharged from the hospital with very good weight bearing with the limb, absence of lameness, pain and swelling. Radiographs demonstrated complete healing of the 2 bones andfilling of bone holes from cortical screws. Discussion: Non-union is one of the most serious complications of fractures in dogs. The reported great percentage of antebrachial non-unions (up to 60% of cases) requires application of a method for bone healing promotion. Bone grafting is a preferred approach, in particular the use of autologous bone grafts that are well integrated in the host bone with minimum risk of infection or displacement. The autologous cancellous bone graft in the dog was applied together with erythropoietin in order to promote bone healing on the basis of previous research data confirming its osteoinductive and angiogenic potential. It stimulates the differentiation of mesenchymal stem cells into osteoblasts, thus improving bone regeneration and speeding bone healing, modulates inflammation by antagonising pro-inflammatory cytokines. Experimental studies in mice, rats and rabbits having explored the local bone regenerating effect of erythropoietin, either alone or with a bone substitute provided histological evidence that erythropoietin stimulated angiogenesis and potentiated the effect of bone substitute and mineralisation at the bone defect site, and increased fibrous tissue and blood vessels formation in treated in comparison to untreated bone defects. In the presented clinical case of atrophic non-union with possibly avascular bone ends, the osteogenic and angiogenic potential of erythropoietin, mixed with the autologous cancellous bone graft for filling of bone defect and bone holes from cortical screws, resulted in bone healing over a very short period with excellent clinical outcome. Therefore, erythropoietin appears a promising adjunct to the functional therapy for bone non-union regeneration. Keywords: Pomeranian, dog, bone graft, fracture, traumatic injury, atrophic antebrachial non-union, cancellous autograft.